KUASA WALl MUJBIR: SATU PERBINCANGAN - Azahari, Raihanah (Jurnal Syariah, 2019)
Wali (guardianship) is a condition in solemnizing a marriage and the appointment of a wali is based on the conditions ag reed by the fuqaha. The current discussion attemps to elaborate the authority ofwali mujbir and the agreement of the bride for the marriage to be peiformed as well as to answer the question of whether the authority of wali mujbir applies only to the brides of junior age. References are made to the nos and opinion of thefuqaha.